Konflik Batin Tokoh Iyan Dalam Novel Iyan Bukan Anak Tengah Karya Armaraher: Kajian Psikologi Sastra Sigmund Freud - Rachmah Ega Pramesti; Hespi Septiana (CV. SINAR HOWUHOWU, 2026)
This study aims to describe the forms of inner conflict, the maturation process, and the manifestations of the id, ego, and superego personality structures of the character Iyan in Armaraher's novel